Effect of carbon fiber surface properties on carbon fiber/polyphenylene sulfide composite interfacial property. Issue 3 (14th February 2023) - Yu, Lei; Wang, Kai; Guan, Yanfei; Liu, Zhaobo; Sun, Mingchen; Zhao, Yan
Abstract: Carbon fiber (CF) reinforced polyphenylene sulfide (PPS) composite shows extraordinary thermal stability, chemical resistance, and processability. The interface between CF and PPS transfers the load, and its properties are crucial to determine composite properties such as mechanical performance, reliability, and so forth. This work explores the relationship between surface properties of CFs (with/without sizing layer) and the interfacial properties of CF/PPS composite. X‐ray photoelectron spectroscopy, scanning electron microscopy, atomic force microscope were employed to evaluate surface physicochemical properties of CFs, and reveal the increasing roughness and decreasing content of functional groups on the CF surface after desizing. Inverse gas chromatography and dynamic contact angle tests were adopted to characterize the surface energy of CFs, and present that the dispersive component of surface energy increases, while the polar component decreases, and the total surface energy is barely changed after desizing. Differential scanning calorimetry measurement reveals the increasing crystallinity of CF/PPS after CF desizing. Microbond test was performed to analyze interfacial shear strength (IFSS) of CF/PPS, displays that IFSS keeps almost constant after CF desizing. The results demonstrate that the surface energy of CF is important to the interfacial crystallinity, but not the critical factor for interfacial strength of CF/PPS composite. Abstract : Effect of carbon fiber surface properties on carbon fiber/polyphenylene sulfide composite interfacial property.